Case conceptualization in child welfare: an underused resource to improve child, family, and provider outcomes - McTavish, Jill R.; McHolm, Angela; Niec, Anne; Pietrantonio, Anna Marie; McKee, Christine; MacMillan, Harriet L. (Frontiers in Psychiatry, 2024)
Case conceptualization, formally known as case formulation, is one tool that assists in determining the best course of action for children and families experiencing family violence that has been underutilized in child welfare. In this paper we present a step-by-step case conceptualization process that considers the child welfare context. We then present a hypothetical case example of a 10-year-old child referred by a child welfare worker to evidence-based treatment for mental health and behavioural concerns. Mental health services are not helpful for the child and further consultation is enlisted. To more effectively guide intervention and treatment planning and ultimately improve outcomes for the child, we present case conceptualization as a process to incorporate relevant aspects of the child and family's history and circumstance. We conclude with a succinct case conceptualization and treatment plan to show how the prognosis of the child can be improved when case conceptualization is employed.